The Trinity among the nations : the doctrine of God in the majority world - Green, Gene L.; Pardue, Stephen T.; Yeo, Khiok-Khng (Majority world theology series., 2015)
Though the global center of Christianity has been shifting south and east over the past few decades, very few theological resources have dealt with the seismic changes afoot. The Majority World Theology series seeks to remedy that lack by gathering well-regarded Christian thinkers from around the world to discuss the significance of Christian teaching in their respective contexts. The Trinity among the Nations focuses on Christian understandings of the character and work of God in various contexts. The contributors highlight global trends in trinitarian theology in relation to historic Christian confessions, especially the Nicene Creed, and draw out the rich implications of the doctrine of God for the church and Christian living today.